A Loan-level Investigation of Chinese Credit Guarantee. Issue 6 (1st November 2020) - Fong, Wai-Ming; Liu, Ming; Yu, Xiaojian
Abstract: Using a loan-level dataset on a big private-owned credit guarantor in Guangdong province, we study how the guarantor manages risk. In a typical bank-guarantor collaboration agreement, the bank may cherry-pick a borrower to co-sponsor the loan with the guarantor so as to share the default risk, the guarantee fee and the collateral. Borrowers with no bank co-sponsorship should be riskier than borrowers with bank co-sponsorship, so the guarantor may treat these two types of borrowers differently. We find that the borrowers with guarantor's sole sponsorship pay higher guarantee fee, pledge more collateral, and are granted shorter loan maturity than the borrowers with bank co-sponsorship, and that the loan amount is not affected by the absence of bank's co-sponsorship.